College Students' Coping Strategies for Dating Violence: A Case Study in Padang City - Esi Afriyanti; Olga Mulyanes; Randy Refnandes (Fakultas Keperawatan Universitas Andalas, 2025)
Dating Violence is still a problem in relationships between men and Female. Its prevalence is increasing from year to year, especially among students. Usually, victims will use self-defense (coping) in dealing with this dating violence situation. This study aims to determine the description of coping strategies of students who experience dating violence in the city of Padang. This type of research is descriptive observational research. The population of the study was students who experienced dating violence in two leading institutions in the city of Padang. The sample was obtained using the lemeshow formula of 380 people with a purposive sampling technique. The strategy questionnaire used The Ways of Coping the Revised Version, and dating violence used a questionnaire developed from the theory. The analysis used a frequency distribution. The results of this study indicate that respondents experienced dating violence in the moderate category (66.6%) in both institutions. The type of verbal dating violence that was widely accepted was in the moderate category (60%), while the type of physical dating violence was only in the mild category (64.5%). The coping strategy that was widely used by victims was emotional coping (66.8%). There is a need to develop effective interventions in accordance with the coping chosen to support the well-being of victims of dating violence